(untitled) (Malaysian Management Journal, 2013)
This study focuses on the service quality and customer satisfaction among the private and public sector banks in India. Today customers are supposed to have awareness about the financial services provided by the banking sector. An attempt has therefore, been made in this paper to quantify the ‘awareness level’ of the customers and analyze the ‘service quality experience’ of the customers from their banks. The study has been carried out to compare the service quality experienced by customers of the public and private sector banks and to study the link between service quality and customer satisfaction. For that reason a well structured questionnaire was used to collect the views of customers on various service dimensions and the satisfaction of the customers regarding the services offered by the public and private sector banks. Various statistical tools like ANOVA, Factor Analysis and Multiple Regressions were used for analyzing the data collected on five service dimensions of SERVQUAL and satisfaction of customers. The results indicate that the private sector bank was better in terms of providing services and creating awareness about their products and services. The study also proves that an increase in service quality will most likely lead to customer satisfaction.